Metatarsal osteotomies in Hallux Rigidus - Ferreyra, Martín; Viladot Voegeli, Antonio; Viladot-Pericé (In Memoriam), Ramón (Journal of the Foot & Ankle, 2022)
This work presents the objectives and indications of the three distal osteotomies of the first metatarsal most frequently used in Hallux Rigidus surgery: Weil-Barouk oblique osteotomy, Youngswick (modified Chevron) osteotomy, and Watermann dorsal closed wedge osteotomy. The surgical technique, indications, advantages, and disadvantages of each of them are described. Level of Evidence V; Therapeutic Studies; Expert Opinion.